ANALISA IMPLEMENTASI SMART CITY MADANI PEMERINTAH KOTA PEKANBARU DALAM UPAYA SINERGITAS PROGRAM ASEAN SMART CITIES NETWORK (ASCN) 2030 - Hisra Mariza (Journal of Diplomacy and International Studies, 2019)
In this research will focus on the Analysis of the Smart City Madani Implementation in Pekanbaru City as an effort to synergize the ASEAN Smart Cities Network 2030 Program. The development of Smart City has expanded in various parts of the world. It is contained in The Association of Southeast Asian Nations (ASEAN) has also begun to discuss with Singapore, based on the establishment of the ASEAN Smart City Network (ASCN) 2030. This agreement is related to Indonesian government currently doing with the Movement Towards 100 Smart Cities that encourage the use of technology for advance some cities in order to realize more effective, transparent and reliable governance. As one of the largest cities in Indonesia, of course, rapid development is needed to advance the city, one of them is Pekanbaru. The development of Pekanbaru is achieved with the following 5 points, eg Improving Basic Infrastructure, where to advance Pekanbaru, there are 3 basic infrastructures that must be addressed and developed, eg transportation, electricity and telecommunications; Smart city approach, Pekanbaru approaches to encourage city to become smart cities with the green city approach; Developing the area; Community development; and the formation of quality communities.